Thermodynamic investigations on host/guest complexation in deep eutectic solvent/water mixtures - Nakhle, Lamia; Kfoury, Miriana; Fourmentin, Sophie; Greige-Gerges, Hélène; Landy, David (Comptes Rendus. Chimie, 2024)
The development of formulations based on cyclodextrins (CDs) and deep eutectic solvents (DESs), is an interesting approach to expand the applications of host–guest chemistry. However, there is a lack of information in the literature on the complexation mechanism in these non-conventional media. The aim of this study is to provide, for the first time, fundamental information on the influence of the type and the wt% (weight percent) content of DES in the mixture on the thermodynamic properties (binding strength and complexation mechanism) of a model inclusion complex, β-CD/adamantanol by means of isothermal titration calorimetry (ITC).